The influence of casting currents on the thermal stability of the Cu36Zr48Al8Ag8 amorphous alloy. Issue 5 (26th April 2017) - Li, Xiaoyun; Shen, Yuehua; Cui, Xiao; Zhu, Pantuo; Zhang, Qidong; Huang, Zhongyue; Zu, Fangqiu
Abstract : It is vitally important to understand the thermal stability of amorphous alloys for the potential applications as engineering materials. In this paper, the overheating effects on the thermal stability of Cu36 Zr48 Al8 Ag8 alloys fabricated under different currents were studied. These research results will help to provide a possible route to fabricate amorphous alloys with a better thermal stability and to broaden the industrial application of amorphous alloys. Abstract : The effects of casting currents on the thermal stability of Cu36 Zr48 Al8 Ag8 amorphous alloys were investigated. Differential scanning calorimetry and resistivity experiments show that the activation energy (∆ Ex, ∆ Ep ) of Cu36 Zr48 Al8 Ag8 amorphous alloy increases with elevating currents. Annealing experiments reveal that crystallization of low‐current samples occurs prior to that of high‐current samples. These results indicate that casting currents could enhance the thermal stability of amorphous alloys. The reason is analyzed from the viewpoint of melt state. These results could be used to provide a possible route to fabricate amorphous alloys with improved thermal stability.